Quality service delivery of non-audit services and compliance with international standards on quality control (ISQC) of SMES practitioner and its relationship to satisfaction and nonaudit fees, perceptions of SMES. - Haron, Hasnah (Universiti Sains Malaysia, 2010)

(untitled)
Small and Medium Enterprises (SMEs) are the key market segment for the Small and Medium Practitioners (SMPs) who provide business advisory services, such as accounting, taxation and consulting services to cater to the business needs of the SMEs.